Farmers-Herdsmen Conflict in Africa: The Case of Nigeria - Ejiroghene Augustine Oghuvbu; Oluwatobi Blessing Oghuvbu (Vestnik RUDN. International Relations, 2020)
General population growth and an increase in the number of farmers, environmental degradation, disruption of conditions for resolving land and water disputes, and the proliferation of Small Arms and Light Weapons (SALW) in the Sahel and West Africa have exacerbated the struggle for the survival and security of economic livelihoods, and in particular negatively affected relationships between shepherds and farmers in several communities in Africa. This kind of conflict between farmers and herdsmen mainly applies to Nigeria, but is also present in other African countries, especially in Mali, Burkina Faso, Chad, Senegal, Cameroon, and Côte d’Ivoire. Such conflicts are not triggered by a single reason, but are driven by a set of multi-causal factors, such as scarce resources in the face of greater need, reprisal attacks, land and climate change, etc. Obviously, in case of Nigeria this kind of conflicts have a disintegrative impact, as they lead to the inimical effects to the country’s unity. The need for fostering value reorientation and restoring earlier interactive ties between herdsmen and farmers seems vital today, so that Nigerians can learn to appreciate the values that unite them more than those that separate the society.